Does Chief Executive Officer Succession Affect Firms Financial Performance in Nigeria? - Ojeka, Stephen A.; Adetula, Dorcas T.; Mukoro, Dick O.; Kpokpo, Oyintinane P. (International Journal of Economics and Financial Issues, 2017)
This study examined empirically the impact of Chief Executive Officer (CEO) succession on the financial performance of firms listed on the Nigerian stock exchange. For the purpose of this research, secondary data was used and the instruments of data collection were financial statements. A matched-paired t-test was used in testing the hypothesis. The overall results show that using return on asset, return on equity, return on capital employed and Tobin’s Q as a measure of performance; companies that experienced forced CEO turnovers had disrupted performances and therefore experienced decreased performance following CEO succession. The results also show a significant decline in the performance of companies that had insider successors. However, the study found increase performance in firms where the CEO voluntarily resigns and an outsider took over as the CEO. As CEO succession has a significant impact on subsequent performance of Nigerian firms, this study therefore recommends that board should have well-structured succession plans that would define what exactly is the goal of the firms and the type of successor required to fit in. In addition the apparent successors should be assessed based on the proficiencies needed to achieve high financial and organizational performance and the capabilities and profile necessary to undertake the role of the CEO should be properly defined. This should include a narrative explanation of the required skill, competencies, attitudes, knowledge and other important abilities required for a standard performance. Keywords: Chief Executive Officer Succession, Financial Performance, Nigerian Stock Exchange, Firms and Competencies JEL Classifications: E44, G1